1981
DOI: 10.1002/path.1711350305
|View full text |Cite
|
Sign up to set email alerts
|

The glomerular basal lamina in hereditary nephritis

Abstract: Characteristic ultrastructural alterations of the glomerular basal lamina have been reported in hereditary nephritis. The basal lamina is irregularly thickened and the lamina densa shows replication with a "basket weave" pattern, enclosing electron-lucent lacunae which frequently contain small dense particles. However there is controversy regarding the specificity of this lesion in hereditary nephritis. To determine the specificity, 366 renal biopsies from 310 children were studied retrospectively. Twenty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Hereditary nephropathy (hereditary nephritis) [6,9,[16][17][18][19][20][21][22] often has a progressive course leading to renal failure in the second or third decade, with males more severely affected than females; nerve deafness, eye abnor malities, or other defects are also found in a proportion of cases (Alport's syndrome). Histologically, the GBM may be diffusely thinned, possibly more so in the earlier stages [6,9,20,21], but typically it is abnormally thick and has a multiply split 'basket-weave' lamina densa enclosing dense particles [16][17][18][19], Thin basement membranes are associated more regularly with benign familial hematuria [7][8][9][10]; this condition has generally been regarded as non progressive, but examples of predominantly thin mem brane lesions in young people that have terminated with chronic renal failure have been recorded by Pielet al [9], and others too have suggested that such forms occur [22,23], Our patients do not have the GBM thickening and splitting, or the deafness or other associated symptoms, of hereditary nephropathy as usually described; their ab normally thin basement membrane is indistinguishable from that in benign hematuria, but some have hyperten sion or renal insufficiency. Cases 1, 4, and 10 are 'pro gressive', as evidenced by glomerular sclerosis, tubular atrophy and renal insufficiency; in the remainder the lesion may be 'benign' but those with mild hypertension 26-51 (3 with mild hypertension or minimal elevation of serum creatinine) (cases 7, 13) or minimal azotemia (case 6) are problem atical, pending follow-up (the hypertension could of course be non-renal).…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary nephropathy (hereditary nephritis) [6,9,[16][17][18][19][20][21][22] often has a progressive course leading to renal failure in the second or third decade, with males more severely affected than females; nerve deafness, eye abnor malities, or other defects are also found in a proportion of cases (Alport's syndrome). Histologically, the GBM may be diffusely thinned, possibly more so in the earlier stages [6,9,20,21], but typically it is abnormally thick and has a multiply split 'basket-weave' lamina densa enclosing dense particles [16][17][18][19], Thin basement membranes are associated more regularly with benign familial hematuria [7][8][9][10]; this condition has generally been regarded as non progressive, but examples of predominantly thin mem brane lesions in young people that have terminated with chronic renal failure have been recorded by Pielet al [9], and others too have suggested that such forms occur [22,23], Our patients do not have the GBM thickening and splitting, or the deafness or other associated symptoms, of hereditary nephropathy as usually described; their ab normally thin basement membrane is indistinguishable from that in benign hematuria, but some have hyperten sion or renal insufficiency. Cases 1, 4, and 10 are 'pro gressive', as evidenced by glomerular sclerosis, tubular atrophy and renal insufficiency; in the remainder the lesion may be 'benign' but those with mild hypertension 26-51 (3 with mild hypertension or minimal elevation of serum creatinine) (cases 7, 13) or minimal azotemia (case 6) are problem atical, pending follow-up (the hypertension could of course be non-renal).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed X-linked dominant inheritance in some kindreds (2) is suggested by lack of father to son transmission, severe renal disease in affected males, and asymptomatic microscopic hematuria in most affected females. By ultrastructural analysis, diffuse splitting, and multlamination ofthe lamina densa of the glomerular basement membrane (GBM) with interposed soo-A granular deposits have been recognized and are often demonstrable early in the course of the disease (3)(4)(5)(6)). Antibodies from patients with Goodpasture (GP) syndrome, an autoimmune disease characterized by the presence of circulating and fixed anti-GBM antibodies resulting in severe glomerulonephritis and pulmonary hemorrhage, have been useful probes for analysis of FN.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects were water loaded with 20 ml/kg before the test and then received 5% glucose intravenously at 150 ml/h during the investigation together with tap water ad libitum. Glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) were calculated by measuring the renal clearance of a continuous combined infusion of 5"Cr-EDTA and '25I-hippuran, respectively, after a loading bolus (total dose, 4 MBq). For the first 15 min, 130 mg/kg dextran 70 (peak, 48 A) in 0.9% saline (Baxter Healthcare, Thetford, UK) was infused after the subject had received 20 ml dextran 1 (8) ( 12,13) (Varian Associates Ltd., Walton-upon-Thames, UK) and the total dextran concentration of each 0.2 ml of eluate was integrated using the FPLC microprocessor.…”
Section: Methodsmentioning
confidence: 99%
“…In Alport's, GBM thinning occurs but is patchy. In addition there may be characteristic thickening and splitting ofthe GBM with a basket-weave appearance (4).…”
Section: Introductionmentioning
confidence: 99%